Dialectics for the New Century - Ollman, B. author. aut Link
VII, 262 p.
Keywords: This anthology contains some of the more important Marxist thinkers now working on dialectics. As a whole the book is an unusual 'Introduction to Dialectics', a systematic restatement of what it is and how to use it, a survey of most of the main debates in the field, and a good picture of the current state of the art of dialectics.